Patient centricity as strategy to improve quality of service in healthcare management - Pereira, L.; Jerónimo, C. H.; Salgado, A.; Dias, Á.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Healthcare Technology and Management, 2023)
The patient experience in hospitals regarding treatments of breast cancer can impact their personal strengths to gain motivation to overcome cancer. The goal of this project was to assess the user experience with breast pathology in terms of healthcare and motivation. To evaluate the patient experience, several interviews were conducted with patients with breast pathology during their journey at the institute. This analysis is associated with the ambition not only to better understand the users but also to improve their provision of healthcare. As a result, interviews with health professionals and user family members were also carried out. The interviews were carried out in a semi-structured manner, allowing the parties involved to freely identify what they believe are the major constraints and strengths. The results show that internal process optimisation, professional training, infrastructures improvement, information sessions and co-creation sessions can improve quality of service in healthcare management.